2022
DOI: 10.3390/children9081128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health Literacy Assessment Tools among Beijing School-Aged Children

Abstract: Health literacy is a broad and multidimensional construct, making its measurement and conclusions inconsistent. This study aims to compare the patterning of health literacy using different assessment tools and examine their impact on children’s developmental outcomes. A cross-sectional study was conducted with 650 students in Years 7–9 from four secondary schools in Beijing. Health literacy was measured by the eight-item health literacy assessment tool (HLAT, score range 0–37), the six-item Newest Vital Sign (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
0
4
0
3
Order By: Relevance
“…Essa pontuação representa cerca de 68% da pontuação máxima possível de LS (37 pontos) pela referida escala. Outros estudos (49)(50)(51)…”
Section: Discussionunclassified
“…Essa pontuação representa cerca de 68% da pontuação máxima possível de LS (37 pontos) pela referida escala. Outros estudos (49)(50)(51)…”
Section: Discussionunclassified
“…In the global health promotion agenda of the World Health Organization (WHO) (4), addressing low health literacy is a part of the strategy to tackle health inequities (5). Many national governments and international organisations have integrated health literacy into their health agendas and initiatives and even developed national action plans to improve population health literacy and reduce health disparities (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Child health inequities manifest not only in distal outcomes such as body mass index, diet patterns, and physical activity but also in generic health literacy, which is both a determinant of health and an immediate health outcome. Guo et al [ 8 ] investigated health literacy among 650 middle school students in Beijing and found that the distribution of health literacy varied by year level, ethnicity, family composition, family socioeconomic position, and personal health interests. The work of Krenz et al [ 5 ] also showed that children from socioeconomically disadvantaged backgrounds had lower scores of physical health literacy than their advantaged peers.…”
mentioning
confidence: 99%